Pemetaan Kelompok Belajar dalam Pembelajaran Berdiferensiasi Pada Mata Pelajaran Bahasa Indonesia - Bangun, Wendy Fernando; Zarra, Merlin; Abrar, Mukhlash; Priyanto, Priyanto (STKIP Siliwangi, 2025)
Differentiated learning is a new learning approach in Indonesian education. There are still many misconceptions about it, especially in the mapping learning groups. Still, many teachers map students based on learning styles and cognitive levels. This is prohibited in differentiated learning. Thus, this research aims to describe how learning group mapping in differentiated learning in Indonesian language subjects. The method used is library research through scientific research from several sources such as books, relevant research results, and articles from various journals. Based on the research results, learning group mapping is classified based on learning readiness, students' initial understanding of the material to be learned, or based on students' interests. In the context of Indonesian language learning, teachers can consider learning readiness through learners' language skills capital, initial understanding of Indonesian language material to be learned, and learners' interests in the context of Indonesian language learning. The results of this study hoped to be a source of reference for other researchers or teachers when determining study groups. Other researchers can also further research by looking at its effectiveness quantitatively.